1999
DOI: 10.1002/etc.5620181205
|View full text |Cite
|
Sign up to set email alerts
|

Effects and bioavailability of 2,4,6‐trinitrotoluene in spiked and field‐contaminated soils to indigenous microorganisms

Abstract: The response of potential nitrification activity (PNA), nitrogen‐fixation activity (NFA), and dehydrogenase activity (DHA) in soil to 2,4,6‐trinitrotoluene (TNT) was assessed. Two garden soils of contrasting texture (sandy loam vs clay loam) were spiked with TNT (25–1,000 mg TNT/kg). Soil microbial activities and TNT residues were analyzed 1 week later. The estimated IC50 (concentration causing 50% inhibition) ranged from 39 to 533 mg/kg of the acetonitrile‐extractable (AE) TNT (1 week after spiking), dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 36 publications
5
29
0
Order By: Relevance
“…Fast degradation to aminated transformation products was reported for TNT [10,18,27] and for the related compounds trinitrobenzene [15,18] and 2,6-dinitrotoluene [17,23]. The inverse relationship between spiking level and magnitude of degradation observed in this study has been reported previously for TNT and related compounds in sediments [10,15,18] and soils [29,30]. It has been demonstrated that this pathway is preferable thermodynamically [28].…”
Section: Fate Of Tntsupporting
confidence: 83%
“…Fast degradation to aminated transformation products was reported for TNT [10,18,27] and for the related compounds trinitrobenzene [15,18] and 2,6-dinitrotoluene [17,23]. The inverse relationship between spiking level and magnitude of degradation observed in this study has been reported previously for TNT and related compounds in sediments [10,15,18] and soils [29,30]. It has been demonstrated that this pathway is preferable thermodynamically [28].…”
Section: Fate Of Tntsupporting
confidence: 83%
“…Typically, it is assumed that ammonia‐oxidizing bacteria are the most susceptible to pollution [22], yet the correlation between TNT levels in soil and ammonia‐oxidizing ability can be quite low, e.g. r 2 =0.393 [3] and r 2 =0.49 [23]. In contrast, in this study, denitrification activity was strongly negatively correlated, r 2 ≥0.90, with TNT concentrations in soil.…”
Section: Discussionmentioning
confidence: 50%
“…The extensive manipulation required for the assessment of nitrification activity and prolonged incubation under slurry conditions may be responsible for the differences seen between these two assays [24]. Despite these differences, the IC 50 values for nitrification and denitrification at this field site were similar with an IC 50 of 51 mg TNT kg −1 soil for nitrification [23] and 26 mg TNT kg −1 soil for N 2 OR activity.…”
Section: Discussionmentioning
confidence: 86%
“…The lowest concentration at which RDX had observable negative effects on the measured parameters was 1235 mg RDX (kg soil) −1 . In contrast, another widely used explosive, TNT, inhibited the same metabolic activities at only 1–2 mg TNT (kg soil) −1 [26].…”
Section: Introductionmentioning
confidence: 95%